2011
DOI: 10.1002/hep.24568
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expansion of a unique stem cell population from adult mouse gallbladder

Abstract: The identification of resident stem cells in the mouse gallbladder is to date, unexplored. In addition, the relationship between adult gallbladder stem cells and intrahepatic bile duct (IHBD) cells is not well understood. The goal of this study was to isolate stem cells from an adult mouse gallbladder and determine if they were unique compared to IHBD cells. By limiting dilution analyses and index sorts, we found that an EpCAM+CD49fhi sub-population from primary gallbladder is enriched in colony forming cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…Recently, Spence et al (8) by using a PDX1-Cre transgenic mouse showed that hepatocytes and IHBD cells descend from Pdx1− cells while the EHBD cells including the ventral pancreas derive from Pdx1+ cells. These data were corroborated by a study in our lab, where we found that adult mouse gallbladder stem cells have a distinct phenotypic and expression profile compared to adult mouse IHBD cells (9). However, the differences between human IHBD and EHBD cells have not yet been explored.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Recently, Spence et al (8) by using a PDX1-Cre transgenic mouse showed that hepatocytes and IHBD cells descend from Pdx1− cells while the EHBD cells including the ventral pancreas derive from Pdx1+ cells. These data were corroborated by a study in our lab, where we found that adult mouse gallbladder stem cells have a distinct phenotypic and expression profile compared to adult mouse IHBD cells (9). However, the differences between human IHBD and EHBD cells have not yet been explored.…”
Section: Introductionsupporting
confidence: 83%
“…We identify an EpCAM+CD13+CD44+ epithelial subpopulation from primary human fetal gallbladder that can expand in vitro through seven passages, exhibits single-cell self-renewal and engrafts in the subcutaneous space of immunodeficient mice. Last, we found that expanded human IHBD cells and gallbladder cells had distinct phenotypic and expression profiles with many of the predicted functional differences between both cell types mirroring those from our previous report (9). To our knowledge, this is the first report to prospectively isolate a clonogenic epithelial population from human fetal gallbladder and evaluate its genealogy relative to IHBD cells.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…The extrahepatic biliary tree (comprised of extrahepatic bile ducts, common duct, cystic duct and gallbladder) shares a common progenitor with the ventral pancreas during embryonic development [1]. In the adult, putative facultative stem/progenitor cells are postulated to exist in injured liver [26], pancreas [7], and the extrahepatic biliary system [812]. …”
Section: Introductionmentioning
confidence: 99%